Efficient enzymatic cyclization of an inhibitory cystine knot‐containing peptide. Issue 10 (9th August 2016) - Kwon, Soohyun; Bosmans, Frank; Kaas, Quentin; Cheneval, Olivier; Conibear, Anne C.; Rosengren, K. Johan; Wang, Conan K.; Schroeder, Christina I.; Craik, David J.
ABSTRACT: Disulfide‐rich peptides isolated from cone snails are of great interest as drug leads due to their high specificity and potency toward therapeutically relevant ion channels and receptors. They commonly contain the inhibitor cystine knot (ICK) motif comprising three disulfide bonds forming a knotted core. Here we report the successful enzymatic backbone cyclization of an ICK‐containing peptide κ‐PVIIA, a 27‐amino acid conopeptide from Conus purpurascens, using a mutated version of the bacterial transpeptidase, sortase A. Although a slight loss of activity was observed compared to native κ‐PVIIA, cyclic κ‐PVIIA is a functional peptide that inhibits the Shaker voltage‐gated potassium (Kv) channel. Molecular modeling suggests that the decrease in potency may be related to the loss of crucial, but previously unidentified electrostatic interactions between the N‐terminus of the peptide and the Shaker channel. This hypothesis was confirmed by testing an N‐terminally acetylated κ‐PVIIA, which shows a similar decrease in activity. We also investigated the conformational dynamics and hydrogen bond network of cyc‐PVIIA, both of which are important factors to be considered for successful cyclization of peptides. We found that cyc‐PVIIA has the same conformational dynamics, but different hydrogen bond network compared to those of κ‐PVIIA. The ability to efficiently cyclize ICK peptides using sortase A will enable future protein engineering for this class of peptides and may help in the development of novel therapeutic molecules. Biotechnol. Bioeng. 2016;113: 2202–2212. © 2016 Wiley Periodicals, Inc. Abstract : The bacterial enzyme sortase A was used to cyclize a disulfide‐rich conotoxin containing a cystine knot that was previously intractable to cyclization using chemical synthetic methods. The cyclization was efficient and maintained the overall backbone structure.